Assessing Predicting Factors: Good Management Practices Towards the Successful Implementation of Green Supply Chain Management (GSCM) in IBS Construction Project - Sharifah NurFarhana, Syed Sahimi; Rohana, Mahbub; Afzan, Ahmad Zaini; Nadia, Zaini; Yon Syafni, Samat (CIDB Malaysia, 2021)
The increasing push to use Industrialised Building System (IBS) in the current Malaysian construction industry has opened up opportunities for the implementation of Green Supply Chain Management (GSCM) in IBS to optimise the advantage of environmental sustainability and the green concept. This research aims to investigate the relationship of good management practices towards the successful implementation of GSCM in IBS construction project by adopting a quantitative method through a questionnaire survey and qualitative method to verify the responses. A total of 30 valid responses were analysed by using Regression method. The response obtained is within the IBS key players and evaluated using regression analysis. The results are validated by three (3) IBS industry experts to identify the relationship between good management practices towards successful GSCM implementation in IBS construction. Preliminary findings from the analysis found that all the management practices are significant to the successful implementation of GSCM in IBS construction. Successful implementation will lead to the investigation on how the performance of GSCM can help to digitalize the supply chain management towards the Fourth Industrial Revolution (IR 4.0) in IBS construction.